KUALITAS PELAYANAN DAN PERSEPSI SEMANGAT KERJA PEGAWAI DALAM MENINGKATKAN KEPUASAN MASYARAKAT - Sri Anggun Antu; Syarwani Canon; Melizubaida Mahmud; Irwan Yantu; Maya Novrita Dama (Universitas Negeri Gorontalo, 2026)
This study aims to determine the effect of service quality and employee work motivation on community satisfaction at the Karya Indah Village Office in Asparaga Subdistrict, Gorontalo Regency. Data were collected through the distribution of questionnaires. The population for this study consisted of 200 people, while the sample size was 40 people. The data were analyzed using multiple linear regression. The results show that service quality and employee work ethic have a positive effect on public satisfaction at the Karya Indah Village Office in Asparaga Subdistrict, Gorontalo Regency. Together, these two variables explain public satisfaction with the services provided. This indicates that the better the quality of service provided and the higher the employees’ work ethic, the higher the level of public satisfaction with the services at the Karya Indah Village Office in Asparaga Subdistrict, Gorontalo Regency.